Bedside Lung Ultrasound in the Assessment of Volume Status in Chronic Hemodialysis Patients - Ghita El Bardai; Fadoua Dami; Hakim Hanin; Nadia Kabbali; Mohamed Arrayhani; Tarik Sqalli Houssaini (Journal of Nephrology Advances, 2016)
Introduction: Sonographic B-lines, also known as lung comets, have been shown to correlate with the presence of extravascular lung water. The aim of this study is to assess if chest ultrasound could detect lung water imbibition and its variations induced by dialysis, an experimental model of controlled rapid fluid loss. Methods: A cross-sectional study was conducted in a hemodialysis center in the city of Fez. Lung ultrasounds, impedance measurement, and ultrasound of the inferior vena cava were achieved 30-60 minutes before and after the hemodialysis session. Results: The values, measured by the different techniques used, decrease significantly after hemodialysis (p <0.001). The values studied before and after the hemodialysis, had shown a significant correlation between the results of the impedance measurement, lung ultrasound, and the maximum and minimum of the VCI index diameter and its collapsibility. The decrease in B-lines was correlated with weight decrease during dialysis (p0.005); none of the parameters concerning the IVC were correlated with fluid removal. Conclusion: ultrasound performed at the bedside is now emerging as a reliable, easy-to-apply, and safe method for measuring both lung water and intravascular overload and their decrease after dialysis even on asymptomatic patients. These observations strongly support the use of lung ultrasound in estimating volume overload and monitoring the response to therapy in hemodialysis patients.
Keywords: Ultrasound lung